Efficacy of Centanafadine for Executive Functioning and Learning Problems in Children and Adolescents with Attention-Deficit/Hyperactivity Disorder. - Wilens, Timothy E.; Oberdhan, Dorothee; Jin, Na; Skubiak, Taisa; Childress, Ann C.; van Stralen, Judy; Ward, Caroline L. (Journal of Child & Adolescent Psychopharmacology, 2026)
Objective: The objective of these analyses was to evaluate the efficacy of centanafadine for treatment of attention-deficit/hyperactivity disorder (ADHD) associated features of executive functioning and learning problems measured over 6 weeks in children and adolescents with ADHD. Methods: Two phase 3, randomized, double-blind, placebo-controlled trials were conducted in children and adolescents with a primary diagnosis of ADHD at sites in the United States and Canada. Data presented here are from the total population of children aged 6–12 years (NCT05428033) or adolescents aged 13–17 years (NCT05257265) who received high-dose centanafadine or placebo for 6 weeks. Secondary and other efficacy endpoints assessed change from baseline in the Conners 3–Parent Short Executive Functioning and Learning Problems Content Scale T-scores and the Conners 3–Self-report Short Learning Problems Content Scale T-scores, all analyzed using a mixed-effect model for repeated measures. Clinically meaningful within-patient change and findings from a caregiver and/or adolescent self-report exit survey are also presented. Results: Overall, 76.5% (367/480) of children (mean age 9.2 years, 41.7% female) and 80.8% (371/459) of adolescents (mean age 14.7 years, 40.7% female) completed their respective studies. There were clinically significant improvements with centanafadine treatment observed as early as Week 1 in the Conners 3–Parent Short Executive Functioning (T-score least squares mean change from baseline [standard error] to Week 6: children, −6.8 [1.1] vs. −11.3 [1.1], p = 0.0026 and adolescents, −8.1 [1.0] vs. −13.0 [1.0], p = 0.0003) and Learning Problems content scale T-scores when compared to placebo (children, −8.2 [1.0] vs. −2.8 [0.9], p < 0.0001 and adolescents, −8.0 [0.9] vs. −3.1 [0.9], p < 0.0001). Similar changes from baseline were observed by adolescent self-report (−6.1 [0.9] vs. −2.5 [0.9], p = 0.0023). Compared to placebo, there was a 50% and 88% greater chance of experiencing clinically meaningful within-patient change in executive functioning for children and adolescents, respectively, and a 79% and 81% chance for experiencing clinically meaningful within-patient change in learning problems, respectively. Exit survey data support findings from clinical outcome measures. Conclusions: In addition to its impact on the core symptoms of ADHD, centanafadine improved executive functioning, learning problems, and impact on daily tasks in children and adolescents with ADHD.